2020
DOI: 10.1111/jgh.14960
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of stents in endoscopic ultrasonography‐guided peripancreatic fluid collection drainage: A systematic review and network meta‐analysis

Abstract: Background Although many studies have reported the efficacy of different stents for endoscopic ultrasonography (EUS)‐guided peripancreatic fluid collection (PFC) drainage, they have not completely determined which stent is superior. This network meta‐analysis comprehensively evaluated the comparative efficacy of stents used in EUS‐guided PFC. Methods We searched all relevant studies published up to February 2019 that examined the efficacy of double pigtail plastic stent (DPPS), fully covered self‐expanding met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…10 Some previous studies showed that LAMS may be associated with a higher rate of adverse events. 11,12 Although several systematic studies have compared the safety and efficacy between LAMS and DPPS, there remains a lack of high-quality evidence, and the sample sizes in previous studies were small. In addition, several recent studies have been published.…”
mentioning
confidence: 99%
“…10 Some previous studies showed that LAMS may be associated with a higher rate of adverse events. 11,12 Although several systematic studies have compared the safety and efficacy between LAMS and DPPS, there remains a lack of high-quality evidence, and the sample sizes in previous studies were small. In addition, several recent studies have been published.…”
mentioning
confidence: 99%
“…Stent migration is an adverse effect of EUS‐guided pancreatic drainage and other EUS interventions 2 . Removal of the migrating stent carries risk of bleeding due to scratching injury of the fistula.…”
Section: Discussionmentioning
confidence: 99%
“…It sometimes results in walled‐off necrotic fluid collection 1 . Endoscopic ultrasound‐guided drainage of necrotic fluid collection has become the first line treatment deploying either lumen‐apposing metallic stent (LAMS) or double‐pigtail plastic stent (DPPS) 2 . One of the adverse effects of such procedure is stent migration.…”
Section: Introductionmentioning
confidence: 99%
“…Even though some studies show LAMS might have a slight advantage over plastic stents in terms of clinical success[ 27 , 59 , 60 ], more studies have shown that there were no differences between LAMS and plastic stents regarding the technical success rate, clinical success, recurrence in drainage of pancreatic, and peripancreatic collections[ 24 , 25 , 60 - 62 ]. In contrast, the bleeding risk (including pseudoaneurysm bleeding, which is life-threatening and may require immediate interventional radiology-guided coil embolization or open surgery) is higher in the LAMS group[ 32 , 61 , 62 ]. Moreover, in an RCT, non-superiority of LAMS over plastic stents was observed, and stent-related adverse events and procedure costs of LAMS were higher[ 63 ].…”
Section: Walled Off Necrosismentioning
confidence: 99%